2000
DOI: 10.1117/12.396450
|View full text |Cite
|
Sign up to set email alerts
|

<title>Experimental study of micro-EDM machining performances on silicon wafer</title>

Abstract: The micro-EDM silicon machining performances have been studied on a highly doped P-type { 100) silicon wafer. To demonstrate and to emphasis the special performances of silicon micro-EDM, one kind of stainless steel is machined as a reference material. Both materials are sparked with specific sparking energy in micro-Joule energy range and machining characteristics such as material removal mechanism, cutting rate, relative electrode wear ratio and surface quality are examined and analyzed. The thermally induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…It should be noted that no cracks are visible after the recast layer is removed. This is an indication that the EDM settings (150 V, 3.3 nF) remove the material by melting and not thermal spalling, which would cause thermal shocks and cracks (Song et al 2000). The pre-etch is then followed by etching using HNO 3 :HF mixed in the ratio 4:1 by volume, again for 1 min.…”
Section: Recast Layer Removal Through Etchingmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that no cracks are visible after the recast layer is removed. This is an indication that the EDM settings (150 V, 3.3 nF) remove the material by melting and not thermal spalling, which would cause thermal shocks and cracks (Song et al 2000). The pre-etch is then followed by etching using HNO 3 :HF mixed in the ratio 4:1 by volume, again for 1 min.…”
Section: Recast Layer Removal Through Etchingmentioning
confidence: 99%
“…Heeren et al (1997) successfully fabricated an actuator and sensor using sinker EDM from silicon. Song et al (2000) have investigated the effects of machining characteristics of sinker EDM on silicon.…”
Section: L-wedm Of Siliconmentioning
confidence: 99%
“…Thus, this paper investigates the use of wire electrical discharge machining (WEDM) as an alternative process for machining germanium to reduce or even eliminate subsurface damage. Several authors in the past have experimented with EDM of silicon (Luo et al, 1992;Peng and Liao, 2003;Song et al, 2000;Reynaerts et al, 1998;Kunieda and Ojima, 2000;Uno et al, 1999). Luo et al (Luo et al, 1992) and Peng and Liao (Peng and Liao, 2003) investigated the use of WEDM for slicing of silicon wafers.…”
Section: Introductionmentioning
confidence: 99%
“…Luo et al (Luo et al, 1992) and Peng and Liao (Peng and Liao, 2003) investigated the use of WEDM for slicing of silicon wafers. Song et al (Song et al, 2000) investigated the performance of micro-EDM on highly doped p-type silicon wafers. It was found that not only melting and evaporation but also thermal spalling plays a significant role in the material removal mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive Si3N4-, ZrO2-and Al2O3-based ceramic composites, which have excellent performances in high temperature and high stress applications such as micro gasturbines, can also be machined by micro-EDM [3]. More extended applications are the machining of semi-conducting materials such as silicon [4] and even insulating ceramics like Si3N4 using conductive assisting electrodes [5]. In addition, the implementation of high frequency electrical components in pulse generators, development of accurate motion drive devices and the availability of advanced CNC systems, allows high precision manufacturing and complex 3D micro-structuring [6][7][8].…”
Section: Introductionmentioning
confidence: 99%